Racial demographics and COVID-19 confirmed cases and deaths: a correlational analysis of 2886 US counties - Mahajan, Uma V; Larkins-Pettigrew, Margaret (Journal of public health (Oxford, England), 2020)
Recent news reports state that racial minority groups, such as African-Americans, are experiencing a greater COVID-19 burden, as measured by confirmed cases and deaths. Limited racial data is available on a national level. We conducted the first nationwide analysis to examine COVID-19 and race on a county level. We obtained datasets on COVID-19 cases and deaths, and racial population totals, by US county. We examined if correlations exist between the racial percentages and percentages of confirmed COVID-19 cases and deaths by county. A positive correlation existed between percentages of African-Americans living in a county and who have COVID-19 (r = 0.254, P < 0.0001), who have died from COVID-19 (r = 0.268, P < 0.0001), and case mortality (r = 0.055, P = 0.003). Positive correlations also existed between percentages of Asian-Americans living in counties and these factors. Negative correlations existed between percentages of Whites living in counties and these factors. A weak, albeit very significant, positive relationship exists between the percentage of African-Americans living in a county and the percentage of COVID-19 confirmed cases, confirmed deaths and case mortality in the county. This is in support of many city and statewide analyses, and we urge for targeted resources towards work that further examine these racial associations.